Indonesian Language Learning Strategy for Foreign Speakers Using the Sangiran Museum: Case Study of TISOL Learners from Kokushikan University - Mukhibun, Akhmad; Andayani, Andayani; Suhita, Raheni (Journal of Learning Improvement and Lesson Study, 2024)
Teaching Indonesian to speakers of other languages (TISOL) has been taught in 54 countries. This makes TISOL teaching must be done creatively and innovatively to succeed in internationalizing the Indonesian language. One of the interesting TISOL teaching is tourism-based teaching. This study aims to explain the TISOL learning process at UPT P3B Sebelas Maret University for Japanese Kokushikan University students through the use of educational tourism at Sangiran Museum. This research is qualitative research through a case study approach. Data and data sources in this study are in the form of Indonesian language learning events at Sangiran Museum for 18 TISOL students from Kokushikan University. Data collection techniques were carried out by participatory observation and in-depth interviews with TISOL teachers. Data credibility test was conducted by triangulating data sources and triangulating methods. The results showed that (1) Sangiran Museum can be utilized in TISOL learning about tourism material in Indonesia. (2) The implementation strategy is using a discovery learning model that is applied contextually. (3) The implication of this learning raises learning motivation, improves language skills in reading, listening, writing, and speaking, and can interact with Indonesian native speakers. This research is expected to increase the scientific treasures of TISOL and its teaching strategies.